(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Fetus papyraceus is a rare condition of a mummified and compressed fetus occurring in multiple gestations where one fetus dies in utero and is merged between the uterine wall and the membranes of living fetus. The blood vessels of the placenta of the two fetuses anastomose with each other, a third cycle occurs, causing fetal death (fetal transfer syndrome). Ultrasonography may identify the Fetus papyraceus, but is not always promising due to anatomical location. Cautious supervision is important during pregnancy for its positive outcome. We report a case of fetus papyraceus in Department of Gynecology and Obstetrics, Paropakar Maternity and Women’s Hospital, Kathmandu, Nepal.